2004
DOI: 10.1074/jbc.m407057200
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Gene Disruption Reveals the Role of the Cysteinyl Leukotriene 2 Receptor in Increased Vascular Permeability and in Bleomycin-induced Pulmonary Fibrosis in Mice

Abstract: The cysteinyl leukotrienes (cys-LTs) mediate both acute and chronic inflammatory responses in mice, as demonstrated by the attenuation of the IgE/antigen-mediated increase in microvascular permeability and of bleomycin-induced pulmonary fibrosis, respectively, in a strain with targeted disruption of leukotriene C 4 synthase to prevent cys-LT synthesis. Our earlier finding that the acute, but not the chronic, injury was attenuated in a strain with targeted disruption of the cysteinyl leukotriene 1 (CysLT 1 ) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
110
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(116 citation statements)
references
References 49 publications
2
110
1
2
Order By: Relevance
“…We and others subsequently reported that the mouse CysLT 1 R can function as a receptor for LTD 4 in transfected cells with a ligand preference similar to that of the human CysLT 1 R (20, 21) and that the mouse CysLT 2 R exhibits a ligand profile of LTC 4 Ն LTD 4 Ͼ LTE 4 (21, 22). Targeted disruption of LTC 4 synthase, CysLT 1 R, and CysLT 2 R in mice confirmed the function of the cys-LTs in vascular smooth muscle and in the cellular aspects of allergic or chronic fibrotic pulmonary injury (23)(24)(25)(26)(27)). An additional receptor in porcine pulmonary arterial rings that is responsive to LTC 4 and LTD 4 , but not LTE 4 , has been recognized by differential pharmacologic responses or resistance to available receptor antagonists on various smooth muscle preparations (28,29).…”
mentioning
confidence: 64%
“…We and others subsequently reported that the mouse CysLT 1 R can function as a receptor for LTD 4 in transfected cells with a ligand preference similar to that of the human CysLT 1 R (20, 21) and that the mouse CysLT 2 R exhibits a ligand profile of LTC 4 Ն LTD 4 Ͼ LTE 4 (21, 22). Targeted disruption of LTC 4 synthase, CysLT 1 R, and CysLT 2 R in mice confirmed the function of the cys-LTs in vascular smooth muscle and in the cellular aspects of allergic or chronic fibrotic pulmonary injury (23)(24)(25)(26)(27)). An additional receptor in porcine pulmonary arterial rings that is responsive to LTC 4 and LTD 4 , but not LTE 4 , has been recognized by differential pharmacologic responses or resistance to available receptor antagonists on various smooth muscle preparations (28,29).…”
mentioning
confidence: 64%
“…However, these proinflammatory activities may be attenuated by COX-2 and DSCR1 up-regulation, as noted above. That the cysLT 2 -R mediates subacute types of fibroproliferative lung injury in vivo in response to bleomycin has recently been reported in cysLT 2 -R-deficient mice (40,41). Our data are consistent with the possibility that biological activities of the 5-LO pathway may result in lasting alterations of the EC phenotype, such as increased platelet-EC interactions, promotion of blood monocyte adhesion to the endothelium, participation in extracellular matrix remodeling, and reperfusion injury of the heart (40,41).…”
Section: Discussionmentioning
confidence: 96%
“…That the cysLT 2 -R mediates subacute types of fibroproliferative lung injury in vivo in response to bleomycin has recently been reported in cysLT 2 -R-deficient mice (40,41). Our data are consistent with the possibility that biological activities of the 5-LO pathway may result in lasting alterations of the EC phenotype, such as increased platelet-EC interactions, promotion of blood monocyte adhesion to the endothelium, participation in extracellular matrix remodeling, and reperfusion injury of the heart (40,41). The shared activities of LTD 4 and thrombin invite examination of the possibility that still further actions of thrombin in vivo may also be relevant for LTD 4 actions on EC cysLT 2 -R (20,42).…”
Section: Discussionmentioning
confidence: 96%
“…Ltc4s -/-mice were generated on a 129Sv background (37) and backcrossed for 15 generations onto the C57BL/6 background. Cysltr1 -/-and Cysltr2 -/-mice were generated on a C57BL/6 background as reported previously (38,39). C57BL/6 Gpr99 +/-mice were obtained from the National Institutes of Health Knock-Out Mouse Project and intercrossed to obtain Gpr99 -/-mice (25).…”
Section: Methodsmentioning
confidence: 99%